Hubungan Antara Kematangan Emosi dengan Perilaku Konsumtif pada Mahasiswi di Universitas Muhammadiyah Sidoarjo - Illahi, Ristu Adi Putri; Widyastuti (Indonesian Journal Publisher, 2023)
The purpose of this research is to find out whether there is a relationship between emotional maturity and consumptive behavior among female students at the Muhammadiyah University of Sidoarjo. This study used a quantitative approach, with a population of 1,323 female students, with a sample of 250 female students. The sampling technique used is the probability sampling technique, the measuring tool used is the Likert scale, which is to measure the scale of emotional maturity and consumptive behavior and the reliability test results on the emotional maturity scale with a total of 27 items, the Cronbach Alpha is 0.785. thus, the emotional maturity scale can be stated as consistent or reliable because the Cronbach Alpha value obtained is greater than 0.60. While the results of the consumptive behavior scale with a total of 21 items, the Cronbach Alpha is 0.863. so, the consumptive behavior scale can be declared reliable because the Cronbach Alpha value obtained is greater than 0.60. the results of the Pearson Correlation value between emotional maturity and consumptive behavior -0.145 > 0.05, with sig. (2-tailed) 0.023 <0.05 which means there is a significant correlation between emotional maturity and consumptive behavior. The conclusion from this study is that there is a negative relationship between emotional maturity and consumptive behavior in female students at the Muhammadiyah University of Sidoarjo. By using a measuring tool for emotional maturity and consumptive behavior with the help of SPSS ver. 16 for windows. This can be proven from the results of the analysis which shows a correlation coefficient of -0.145 with a significance of 0.023 <0.05. Thus, it can be explained that the higher the emotional maturity, the lower the consumptive behavior of female students at the Muhammadiyah University of Sidoarjo.